2003
DOI: 10.1162/089892903770007416
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Neuronal Networks Mediate Sustained Attention

Abstract: Abstract& Sustained attention deficits occur in several neuropsychiatric disorders. However, the underlying neurobiological mechanisms are still incompletely understood. To that end, functional MRI was used to investigate the neural substrates of sustained attention (vigilance) using the rapid visual information processing (RVIP) task in 25 healthy volunteers. In order to better understand the neural networks underlying attentional abilities, brain regions where task-induced activation correlated with task per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
196
5
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 284 publications
(231 citation statements)
references
References 43 publications
22
196
5
8
Order By: Relevance
“…This particular sustained attention task is sensitive to dysfunction in the parietal and frontal lobe regions of the brain (e.g. Lawrence et al, 2003), areas also shown to be deficient in dopaminergic activity in chronic cocaine users (e.g. Volkow et al, 1993Volkow et al, , 1997Volkow et al, , 1999Martinez et al, 2007Martinez et al, , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This particular sustained attention task is sensitive to dysfunction in the parietal and frontal lobe regions of the brain (e.g. Lawrence et al, 2003), areas also shown to be deficient in dopaminergic activity in chronic cocaine users (e.g. Volkow et al, 1993Volkow et al, , 1997Volkow et al, , 1999Martinez et al, 2007Martinez et al, , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Medial frontal cortex is highly active at rest, during which it is involved in attentional monitoring of various internal and external stimuli (McKiernan et al, 2003). Medial frontal cortex under-activation during a cognitive task may represent reallocation of limited attentional resources to areas directly involved in task performance (Lawrence et al, 2003;McKiernan et al, 2003). Thus, SWM task demands may be more difficult for younger youths, who require greater attentional allocation to maintain performance, and therefore greater under-activation of medial frontal cortex.…”
Section: Fmri Response and Agementioning
confidence: 99%
“…Many previous studies have implicated these regions (particularly the DLPFC) in top-down control of processing, including the domains of selective attention (Mathalon et al, 2004;Milham et al, 2003), task-switching (Aron et al, 2004;Sussman et al, 2003), spatial attention (Giesbrecht et al, 2003;, sustained attention (Lawrence et al, 2003;Ortuno et al, 2002), emotional (Boshuisen et al, 2002;Milham et al, 2003), and autonomic control (Critchley et al, 2002(Critchley et al, , 2003. The finding that activation in this region (along with the right DLPFC) was significantly greater for No-go trials when compared to the Go trials is also consistent with the studies suggesting it monitors for response conflict Carter et al, 2001), whereby conflict signals the need for the allocation of additional control by the DLPFC (MacDonald et al, 2000).…”
Section: Pfc and Controlmentioning
confidence: 99%